A thorny pathway of macrophage activating factor (GcMAF): from bench to bedside - A. A. Ostanin; S. S. Kirikovich; E. V. Dolgova; А. S. Proskurina; E. R. Chernykh; S. S. Bogachev (Вавиловский журнал генетики и селекции)
Vitamin D3 Binding Protein (DBP) is a multifunctional glycoprotein whose main role is to transport vitamin D3 and its metabolites, but it also is the precursor of the macrophage activating factor (GcMAF). DBP is converted to GcMAF as a result of site-specific selective deglycosylation under the action of β-galactosidase and sialidase, localized on activated B and T cells, respectively. GcMAF exerts its biological activity primarily as the capability of activating macrophages by enhancing their phagocytic function and producing ROS. Activation results in elevated expression of the specific macrophageal surface receptors involved in the recognition of tumor-associated antigens, as well as in the implementation of direct anticancer activity by inducing the apoptosis or necrosis of tumor cells. Increased interest in GcMAF is associated with its potential to be used in the clinic as a new antitumor drug. Besides its anti-tumor activity, GcMAF exerts a potential against a number of viral and neurodegenerative diseases associated with increased activity of N-acetylgalactosaminidase (nagalase) in the blood serum of patients. Nagalase is an enzyme that completely (rather than selectively) deglycosylates DBP so it cannot be converted to GcMAF, leading to immunodeficiency. Circulating DBP is composed of unmodified and O-glycosylated molecules with the glycosylation degree being dependent on the allelic variants of the gene encoding DBP. The role of DBP in the resistance of organism against a number of diseases is supported by the increased risk of a variety of severe illnesses (amyotrophic lateral sclerosis, colorectal cancer etc.) in patients deficient for GcMAF due to homozygosity for defective DBP alleles. In this review, we also will examine in detail the current data i) on the structure and functions of DBP, as the main precursor of GcMAF, ii) on the main mechanisms of GcMAF anticancer effect, iii) on the tumor strategy for neutralizing GcMAF activity, iv) on the results of GcMAF clinical trials in various cancers; and will discuss the available controversies regarding the positioning of GcMAF as an effective antitumor drug.